Cn‐continuity in Digital Image Correlation: Implementation and Validation of C− 1, C0 and C1 Algorithms. (22nd September 2015) - Wittevrongel, L.; Lava, P.; Lomov, S. V.; Debruyne, D.
Abstract: In digital image correlation (DIC), a global approach is more and more used aside from the traditional subset method. The biggest advantages of the global approach are the continuity of the displacement field and the clear link to finite element analysis. In this paper, the traditional subset method is compared to several implementations of the global method, to investigate the importance of continuity in DIC. As first, the most known Q4‐DIC is implemented, where linear elements describe the deformation. The second implementation is the so‐called p‐DIC where the element mesh used in the correlation can be updated to higher‐order elements to describe more complex deformations. The third implementation is a newly proposed C 1 ‐continuous global algorithm. This algorithm is similar to the other global approaches but uses a triangular finite element mesh where the triangular elements within the mesh have a generic p th‐order description. Accordingly, elements can vary both in size and element order to describe more complex deformations while preserving C 1 ‐continuity. The four implementations are made in the same platform, leading to a more robust comparison. In the comparison, both numerical and experimental tests are conducted, and the relation between resolution and special resolution is investigated for all approaches. It is concluded that continuity itself does not have a major influence on the methods performance. The choice of algorithm will be based on the desired specifications of the measurement.